2005
DOI: 10.1038/nn1427
|View full text |Cite
|
Sign up to set email alerts
|

Flexible strategies for sensory integration during motor planning

Abstract: When planning target-directed reaching movements, human subjects combine visual and proprioceptive feedback to form two estimates of the arm's position: one to plan the reach direction, and another to convert that direction into a motor command. These position estimates are based on the same sensory signals but rely on different combinations of visual and proprioceptive input, suggesting that the brain weights sensory inputs differently depending on the computation being performed. Here we show that the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
350
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(382 citation statements)
references
References 32 publications
29
350
3
Order By: Relevance
“…Other V6A cells may use the visual information to monitor the ongoing arm movement, as well as hand/object interaction. These data provide empirical support for computational models suggesting task-dependent reweighting of sensory signals dictated by the information content of the visual feedback when the action occurs (Sober and Sabes, 2005;McGuire and Sabes, 2009). …”
Section: Discussionsupporting
confidence: 57%
“…Other V6A cells may use the visual information to monitor the ongoing arm movement, as well as hand/object interaction. These data provide empirical support for computational models suggesting task-dependent reweighting of sensory signals dictated by the information content of the visual feedback when the action occurs (Sober and Sabes, 2005;McGuire and Sabes, 2009). …”
Section: Discussionsupporting
confidence: 57%
“…First, the reduced speed and completeness of learning in response to larger errors might reflect a change in multisensory integration. Psychophysical studies of human motor control have shown that when integrating sensory signals, subjects can flexibly weight sensory inputs (18,19) and that such weighting appears to be based on the variability of the available sensory signals, as predicted by theories of optimal motor control (20). Such a flexible weighting strategy might account for the inverse relationship between the size of sensory pitch shifts and the magnitude of the behavioral responses.…”
Section: Discussionmentioning
confidence: 99%
“…Other bottom-up influences such as the reliability of sensory (Ernst & Banks, 2002) or sensimotor (Körding & Wolpert, 2004) information, or target modality (Sober & Sabes, 2005) may influence our model's weights, too, but were not within the scope of the current study. Moreover, the present parameter estimates invite the speculation that bottom-up influences, such as the number of stimuli, are reflected in the anatomical weights, whereas top-down influences, such as task instructions, bear on the external weights: Indeed, the anatomical representation of touch is associated with the primary somatosensory cortices, that store all sensory characteristics of a touch.…”
Section: Weighted Integration Accounts For Previous Findingsmentioning
confidence: 93%
“…Yet, to plan actions toward the object, its location must be transformed into another, posture-dependent reference frame (Pouget et al, 2002;Sober & Sabes, 2005). Any perceived tactile stimulus seems to be transformed into an external-spatial reference frame (Driver & Spence, 1998;Yamamoto & Kitazawa, 2001a;Shore et al, 2002;Spence et al, 2004;Soto-Faraco et al, 2004;Röder et al, 2004;Schicke & Röder, 2006;Heed & Azañón, 2014;Heed et al, 2015), even when such recoding is currently not required (Kitazawa, 2002;Azañón et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%